Legal Protection for the Security of Personal Data of Electronic Land Certificate Holders - Primarini, Nabilla Lintang; Rahmalia, Widya Nur; Prihastuti, Devi Indah; Gunawan, Moh. Sigit; Nurhaqi, Ari (Jurnal Legisci, 2025)
Background. The digital shift requires public trust in protecting personal data stored in electronic systems. Law Number 27 of 2022 on Personal Data Protection was enacted to protect personal data owners' rights and specify the obligations of personal data controllers responsible for ensuring data protection. Aim. This study examines the legal protections for personal data security of holders of Electronic Land Certificates issued through Electronic Systems as Electronic Documents. Methods. The writing approach used is normative juridical, employing procedures for collecting and analyzing primary and secondary legal data. Result. The government is responsible for ensuring the security and confidentiality of the Electronic Land Certificate owner's data against breaches. The government, as a data controller, has ensured the protection of personal data for land rights owners in the execution of the electronic certificate program by adopting measures to safeguard Electronic Certificates, including the implementation of the ISO 27001:2013 standard, employing encryption techniques for data storage, utilizing electronic signatures, implementing two-factor authentication, QR Codes, and various additional protective measures. Data controllers are obligated to safeguard data against breaches. The rise of cybercrime accompanies the advancements in information technology. Criminal behavior evolves in response to societal advancements, necessitating ongoing vigilance and proactive measures to anticipate and address emerging abuses. Conclusions. The research findings indicate that the Government, as a data controller, has implemented measures to protect personal data by establishing procedures to secure Electronic Certificates. Implication The implementation of electronic certificates is currently being executed in phases, considering the preparedness of infrastructure, human resources, and maturity levels at each land office to ensure proper execution across all land offices in Indonesia